2021
DOI: 10.3390/rs13163322
|View full text |Cite
|
Sign up to set email alerts
|

Improving Potato Yield Prediction by Combining Cultivar Information and UAV Remote Sensing Data Using Machine Learning

Abstract: Accurate high-resolution yield maps are essential for identifying spatial yield variability patterns, determining key factors influencing yield variability, and providing site-specific management insights in precision agriculture. Cultivar differences can significantly influence potato (Solanum tuberosum L.) tuber yield prediction using remote sensing technologies. The objective of this study was to improve potato yield prediction using unmanned aerial vehicle (UAV) remote sensing by incorporating cultivar inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Potato tuber yield is jointly affected by genetic variation, environmental conditions (soil and weather), seed quality, and crop management practices ( Li et al, 2021a ). Classical potato yield prediction models are often used to estimate yields within the growing season by considering nitrogen fertilizer, temperature, and daylight or the incidence of solar radiation ( Wang X. et al, 2021 ).…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potato tuber yield is jointly affected by genetic variation, environmental conditions (soil and weather), seed quality, and crop management practices ( Li et al, 2021a ). Classical potato yield prediction models are often used to estimate yields within the growing season by considering nitrogen fertilizer, temperature, and daylight or the incidence of solar radiation ( Wang X. et al, 2021 ).…”
Section: Applicationsmentioning
confidence: 99%
“…Unmanned aerial vehicle-based imagery is largely used for predicting potato yield in site-specific studies. Multi- ( Tanabe et al, 2019 ; Li et al, 2021a ) and hyper-spectral ( Li B. et al, 2020 ; Sun et al, 2020 ) have been used to establish and validate a variety of machine learning models for predicting potato yield. The prediction performance of images collected at different growth stages was compared.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspects related to the variability of these factors may pose a particular problem [7]. Many researchers have dealt with this issue with varying degrees of success [8,9,10].…”
mentioning
confidence: 99%
“…Li et al [10] found that accurate, high-resolution yield maps are needed to identify spatial patterns of yield variability, to identify key factors influencing yield variability, and to provide detailed management information in precision farming. Varietal differences may significantly affect the forecasting of potato tuber yields with the use of remote sensing technologies.…”
mentioning
confidence: 99%